Shaping public opinion on the issue of childbirth; a critical analysis of articles published in an Australian newspaper - Francis Karen; McIntyre Meredith J; Chapman Ysanne (BMC, 2011)
Abstract Background The Australian government has announced a major program of reform with the move to primary maternity care, a program of change that appears to be at odds with current general public perceptions regarding how maternity care is delivered. Methods A critical discourse analysis of articles published in 'The Age', a newspaper with national distribution, subsequent to the release of the discussion paper by the Australian Government in 2008 was undertaken. The purpose was to identify how Australian maternity services are portrayed and what purpose is served by this representation to the general public. Results Findings from this critical discourse analysis revealed that Australian maternity services are being portrayed to the general public as an inflexible outdated service struggling to meets the needs of pregnant women and in desperate need of reform. The style of reporting employed in this newspaper involved presenting to the reader the range of expert opinion relevant to each topic, frequently involving polarised positions of the experts on the issue. Conclusions The general public are presented with a conflict, caught between the need for changes that come with the primary maternity model of care and fear that these change will undermine safe standards. The discourse; 'Australia is one of the safest countries in which to give birth or be born, what is must be best', represents the situation where despite major deficiencies in the system the general public may be too fearful of the consequences to consider a move away from reliance on traditional medical-led maternity care.